Yacon (Smallanthus sonchifolius) as a Food Supplement: Health-Promoting Benefits of Fructooligosaccharides - Caetano, Brunno F. R. [UNESP]; Moura, Nelci A. de [UNESP]; Almeida, Ana P. S. [UNESP]; Dias, Marcos C.; Sivieri, Katia [UNESP]; Barbisan, Luis F. [UNESP] (Mdpi Ag, 2016)
Yacon (Smallanthus sonchifolius), a perennial plant of the family Asteraceae native to the Andean regions of South America, is an abundant source of fructooligosaccharides (FOS). This comprehensive review of the literature addressed the role of yacon supplementation in promoting health and reducing the risk of chronic diseases. According to several preclinical and clinical trials, FOS intake favors the growth of health-promoting bacteria while reducing pathogenic bacteria populations. Moreover, the endproducts of FOS fermentation by the intestinal microbiota, short chain fatty acids (SCFA), act as substrates or signaling molecules in the regulation of the immune response, glucose homeostasis and lipid metabolism. As a result, glycemic levels, body weight and colon cancer risk can be reduced. Based on these findings, most studies reviewed concluded that due to their functional properties, yacon roots may be effectively used as a dietary supplement to prevent and treat chronic diseases.
Keywords: yacon; prebiotics; fructooligosacharides; functional food; chronic diseases